Optimizing relapse prevention and changing habits (REACH+) in anorexia nervosa. Issue 6 (30th April 2022) - Steinglass, Joanna E.; Attia, Evelyn; Glasofer, Deborah R.; Wang, Yuanjia; Ruggiero, Julia; Walsh, B. Timothy; Thomas, J. Graham
Abstract: Introduction: Relapse rates in anorexia nervosa (AN) are high, even after full weight restoration. This study aims to develop a relapse prevention treatment that specifically addresses persistent maladaptive behaviors (habits). Relapse Prevention and Changing Habits (REACH+) aims to support patients in developing routines that promote weight maintenance, encourage health, and challenge habits that perpetuate illness. The clinical trial design uses the Multiphase Optimization STrategy (MOST) framework to efficiently identify which components of treatment contribute to positive outcomes. Methods: Participants will be 60 adults with AN who have achieved weight restoration in an inpatient setting. Treatment will consist of 6 months of outpatient telehealth sessions. REACH+ consists of behavior, cognitive, and motivation components, as well as food monitoring and a skill consolidation phase. A specialized online platform extends therapy between sessions. Participants will be randomly assigned to different versions of each component in a fractional factorial design. Outcomes will focus on maintenance of remission, measured by rate of weight loss and end‐of‐trial status. Interventions that contribute to remission will be included in an optimized treatment package, suitable for a large‐scale clinical trial of relapse prevention in AN. Abstract : Relapse rates in anorexia nervosa are high and no intervention has emerged as the treatment of choice to improve outcomes in adults. This clinical trial will identify the components of outpatient treatment that are most successful in helping patients maintain remission. New treatment approaches are needed that can improve outcomes and improve access to specialized care.